Zinc metallothionein imported into liver mitochondria modulates respiration - Ye, Bin (The National Academy of Sciences, 2001)
Metallothionein (MT) localizes in the intermembrane space of liver mitochondria as well as in the cytosol and nucleus. Incubation of intact liver mitochondria with physiological, micromolar concentrations of MT leads to the import of MT into the mitochondria where it inhibits respiration. This activity is caused by the N-terminal β-domain of MT; in this system, the isolated C-terminal α-domain is inactive. Free zinc inhibits respiration at concentrations commensurate with the zinc content of either MT or the isolated β-domain, indicating that MT inhibition involves zinc delivery to mitochondria. Respiratory inhibition of uncoupled mitochondria identifies the electron transfer chain as the primary site of inhibition. The apoform of MT, thionein, is an endogenous chelating agent and activates zinc-inhibited respiration with a 1:1 stoichiometry ([zinc binding sites]/[zinc]). Carbamoylation of the lysines of MT significantly attenuates the inhibitory effect, suggesting that these residues are critical for the passage of MT through the outer mitochondrial membrane. Such an import pathway has been proposed for other proteins that also lack a mitochondrial targeting sequence, e.g., apocytochrome c, and possibly Cox17, a mitochondrial copper chaperone that is the only protein known so far to exhibit significant primary sequence homology to MT. The presence and respiratory inhibition of MT in liver, but not heart, mitochondria suggest a hitherto unknown biological modulating activity of MT in cellular respiration and energy metabolism in a tissue-specific manner.